1995
DOI: 10.1111/j.1468-2850.1995.tb00047.x
|View full text |Cite
|
Sign up to set email alerts
|

The etiology and treatment of domestic violence between adult partners.

Abstract: The field of family violence, although rapidly expanding, remains characterized by large gaps in knowledge regarding both etiology and effective tmatment strategies. The purpose of this article Is to integrate diverse msearch efforts In order t o better understand the etiology, maintenance, and treatment of interpartner violence. Identilied limitations include problems with detinition, and the lack of integrated, multidimensional axplanatory theories, well-controlled treatment outcome studies, and relational-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 117 publications
(236 reference statements)
1
58
0
1
Order By: Relevance
“…For example, Browne and Bassuk (1997) found that a large number of homeless women were survivors of IPV and Lyon (2002) revealed that more than half of women receiving government assistance were also survivors of IPV. Other research has demonstrated that poverty is highly predictive of violence against women (Feldman & Ridley, 1995). This indicates that perhaps IPV has particularly severe consequences for low-income women.…”
Section: Domestic Violence Servicesmentioning
confidence: 96%
“…For example, Browne and Bassuk (1997) found that a large number of homeless women were survivors of IPV and Lyon (2002) revealed that more than half of women receiving government assistance were also survivors of IPV. Other research has demonstrated that poverty is highly predictive of violence against women (Feldman & Ridley, 1995). This indicates that perhaps IPV has particularly severe consequences for low-income women.…”
Section: Domestic Violence Servicesmentioning
confidence: 96%
“…As with other complex problems, single factor theories do not provide satisfactory explanations, as they provide simplistic ways of viewing complex phenomena. In fact, most researchers and counselors in this area utilize ecological and systemic models, which account for some of this complexity by considering multiple factors that influence IPV and women's responses to it in the context of their lives [41].…”
Section: Theories Of Intimate Partner Violencementioning
confidence: 99%
“…Further complicating the picture is the fact that some researchers and clinicians defi ne these terms differently, while others use them interchangeably. For instance, some researchers refer to batterers as any perpetrator of domestic violence while others reserve the term batterer for an individual who uses multiple forms of violence (e.g., physical and psychological abuse) to control his/her partner (Feldman & Ridley, 1995). Thus, when comparing the differences found across studies, one has to be careful to evaluate the different operationalizations of domestic violence.…”
Section: Challenges In the Assessment Of Domestic Violencementioning
confidence: 99%